(untitled) (SCHOOLAR: Social and Literature Study in Education, 2024)
This research aims to design a learning media named CHILLGO to support the speaking skills of the 10th-grade students BDPM (Marketing Online Business) 2 at Vocational High School PGRI 1 Jombang. This research used Research and Development (R&D) as the method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The result obtained from the material validation score was 80% which was in the “Good” category and the result of the media validation score was 80% which was in the “Good” category. The result of the students’ responses score was 95% which was in the “Very Good” category. It can be concluded that CHILLGO media deserves to be tasted and to be applied as a supporting media in a class activity.